Japan’s Expansion into the Dutch East Indies in the Context of the Greater East Asia War (1930–1945): An Economic-Political Approach - Deviana Nurhuda; Tri Yuniyanto (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to analyze Japan’s survival strategy during the Greater East Asia War through its expansion into the Dutch East Indies from 1930 to 1945, as well as its impact on local communities. The main issues examined are the driving factors behind the expansion and the impact of the military occupation on the population. This study employs historical methods, examining primary sources such as newspaper archives and contemporary documentary photographs, as well as secondary sources in the form of books and scholarly articles. The results indicate that the motives for expansion were driven by wartime economic factors, military strategy, and the Hakko Ichiu ideology. The occupation had far-reaching political consequences through the dismantling of long-standing colonial structures, as well as the exploitation of natural and human resources, which worsened the socioeconomic conditions of the population. The study’s conclusion affirms that this expansion was a vital survival strategy for Japan in the face of Western powers.